Metagenomics reveals biogeochemical processes carried out by sediment microbial communities in a shallow eutrophic freshwater lake - Kuang, Bo; Xiao, Rong; Hu, Yanping; Wang, Yaping; Zhang, Ling; Wei, Zhuoqun; Bai, Junhong; Zhang, Kegang; Acuña, Jacquelinne J.; Jorquera, Milko A.; Pan, Wenbin (Frontiers in Microbiology, 2023)
As the largest shallow freshwater lake in the North China Plain, Baiyangdian lake is essential for maintaining ecosystem functioning in this highly populated region. Sediments are considered to record the impacts of human activities. Hence, the abundance, diversity and metabolic pathways of microbial communities in sediments were studied by metagenomic approach to reveal patterns and mechanism of C, N, P and S cycling under the threat of lake eutrophication. The results showed that total nitrogen (TN) content showed a relatively greater impact on bacterial communities than total phosphorus (TP) content. Many genera, with plural genes encoding key enzymes involved in genes, belonging to Proteobacteria and Actinobacteria which were the most main phylum in bacterial community of Baiyangdian sediment were involved in C, N, S, P cycling processes, such as Nocardioides (Actinobacteria), Thiobacillus, Nitrosomonas, Rhodoplanes and Sulfuricaulis (Proteobacteria). For instance, the abundance of Nocardioides were positively correlated to TN, EC, SOC and N/P ratio in pathways of phytase, regulation of phosphate starvation, dissimilatory sulfate reduction and oxidation, assimilatory sulfate reduction, assimilatory nitrate reduction and reductive tricarboxylic acid (rTCA) cycle. Many key genes in C, N, P, S cycling were closely related to the reductive citrate cycle. A complete while weaker sulfur cycle between SO42− and HS− might occur in Baiyangdian lake sediments compared to C fixation and N cycling. In addition, dissimilatory nitrate reduction to ammonia was determined to co-occur with denitrification. C fixation and methane metabolism were analyzed to reveal the pathways of organic matter conversion. Methanogenesis was the main pathway of methane metabolism and the reductive citrate cycle was accounted for the highest proportion of C fixation processes. The abundance of pathways of assimilatory nitrate reduction, denitrification and dissimilatory nitrate reduction of nitrogen cycling in sediments with higher TN content was higher than those with lower TN content. Besides, Nocardioides with plural genes encoding key enzymes involved in nasAB and nirBD gene were involved in these pathways. In this paper, we provide insights to support the study of the relationship between microbial function and biogeochemistry of shallow freshwater lakes distributed globally under the condition of eutrophication.